Design and Optimization of Permanent Magnet Synchronous Motor for Electric Vehicle Applications - Levent, Ahmet Hamdi; Lordoglu, Abdulsamed; Aydeniz, Mustafa Gurkan (IEEE, 2020)
In this study, the design of 50kW permanent magnet synchronous motor (PMSM) for electric vehicle applications is presented. In the design process, initially, main design constraints and requirements for electric vehicle are determined and the main dimensions of the machine are calculated. In order to investigate electromagnetic and operational performances of motor, motor design program based on finite element method was used and the motor is analyzed. Then, size and position of magnets which are effective in the performance of PMSM are optimized and compared with a conventional machine.
Keywords: Electric vehicle; permanent magnet synchronous motor; optimization of PMSM; Magnet optimization; HYBRID; Energy & Fuels; Engineering